THE CONCEPT OF COMMUNICATION OF THE PESULAP MERAH IN TACKLING OCCULT ALTERNATIVE MEDICINE ACCORDING TO THE PERSPECTIVE OF THE ISLAMIC RELIGION - M. Nashoihul Ibad; Novianto Puji Raharjo (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
Occult alternative medicine is a treatment of human health using strange things that are not by reason or methods of treatment in scientific medicine. One of the figures who overcome supernatural medicine by dismantling the actions of shamans under the guise of ustad is the Pesulap Merah on his youtube account